Getting ready for an emotion: specific premotor brain activities for self-administered emotional pictures - Perri, Rinaldo L.; Berchicci, Marika; Lucci, Giuliana; Cimmino, Rocco L.; Bello, Annalisa; Di Russo, Francesco (Frontiers in Behavioral Neuroscience, 2014)
Emotional perception has been extensively studied in literature, but only few studies have investigated the brain activity preceding exposure to emotional stimuli, especially when they are triggered by the subject himself. Here, we sought to investigate the emotional expectancy by means of movement related cortical potentials (MRCPs) in a self-paced task, in which the subjects begin the affective experience by pressing a key. In this experiment, participants had to alternatively press two keys in order to concomitantly display positive, negative, neutral and scramble images extracted from the International Affective Pictures System (IAPS). Each key press corresponded to a specific emotional category and the experimenter communicated the coupling before each trial, so that the subjects always knew the valence of the forthcoming picture. The main results of the present study consist in a bilateral positive activity in prefrontal areas during expectancy of more arousing pictures (positive and negative), and an early and sustained positivity over occipital areas, especially during negative expectancy. In addition, we observed more pronounced and anteriorly distributed Late Positive Potentials (LPPs) components in the emotional conditions. In conclusion, these results show that the emotional expectancy can influence brain activity in both motor preparation and stimuli perception, suggesting enhanced pre-processing in the to be stimulated areas. We propose that before a predictable emotional stimuli both appetitive and defensive motivational systems act facilitating the forthcoming processing of survival-relevant contents, by means of an enhancement of attention towards more arousing pictures.